International Portfolio Analysis and Strategy: The Challenge of the 80s - Wind, Yoram; Douglas, Susan (Journal of International Business Studies, 1981)
This paper suggests an operational approach to strategic planning for international marketing using a portfolio perspective. The need for such a perspective is discussed, followed by an examination of current approaches to international business portfolio analysis and strategic planning. A new approach to international portfolios, based on a combined stochastic dominance and analytic hierarchy process approaches, is suggested. The data requirements and analysis of this approach are outlined and the issues and challenges in the design and implementation of an international business portfolio system are discussed.